(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
With the arrival of COVID-19, educational processes had to adapt to new emerging methodologies for home, which is why this article conducts a literature review that aims to know the adaptations of the evaluation used by teachers in virtual environments in higher education in Ibero-America during the confinement. A literature review was conducted based on a search of documents in the databases Scielo, Redalyc, Dialnet, Scopus and the academic network ResearchGate, where 14 research articles published in the period from 2020 to 2023 are analyzed. Methodological aspects such as the studied population, the instruments used, and the approach to evaluative processes are identified. The COVID-19 generated a redesign in the curricula, replacing face-to-face methodologies by modalities with the use of digital resources, which made possible a development in the evaluation processes; however, it also hindered the continuity of the training processes, due to the digital gaps in competencies, and the use and availability of resources by educational institutions, teachers, and students.